2014
DOI: 10.1136/bcr-2013-202685
|View full text |Cite
|
Sign up to set email alerts
|

Unusual prosthetic femoral head fracture in total hip arthroplasty: ceramic on polyethylene articulation

Abstract: A 68-year-old man with a previous right total hip arthroplasty presented with acute pain in the right hip, and no associated trauma was reported. The previous hybrid arthroplasty consisted of a ceramic femoral head articulating on an ultra-high-molecular-weight polyethylene liner. The unusual diagnosis of fractured ceramic femoral head was made and an urgent revision arthroplasty was performed to remove the ceramic bearing as well as all implants that may have come into contact with the ceramic. This case repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…The high cobalt levels generated through the alumina abrasive condition is unlikely to be encountered clinically, although instances of ceramic head fracture in vivo have been reported leading to substantial damage of the polyethylene liner. 30 33 The damage generated in the heads produced a comparable surface roughness to that observed and commonly reported in retrieved components. 12 …”
Section: Discussionsupporting
confidence: 72%
“…The high cobalt levels generated through the alumina abrasive condition is unlikely to be encountered clinically, although instances of ceramic head fracture in vivo have been reported leading to substantial damage of the polyethylene liner. 30 33 The damage generated in the heads produced a comparable surface roughness to that observed and commonly reported in retrieved components. 12 …”
Section: Discussionsupporting
confidence: 72%
“…Ceramic implants were first used in THA by Boutin in the 1970s11). Ceramic-on-ceramic articulation has gained popularity due to its favorable properties (e.g., low wear rate, low friction coefficient)412). Ceramic materials are frequently preferred in prosthetic applications, especially in patients with long life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…The most important postoperative causes of ceramic fractures are trauma and hip dislocation6). However, atraumatic spontaneous fractures are not uncommon451516). Other risk factors for ceramic component fractures are high level of activity and obesity13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Tucker and Acharya documented a fracture of a zirconia ceramic femoral head on UHMWPE. 13 In 2006, Habermann et al reported three COP femoral head fractures with impingement of the femoral head, too vertical acetabular cup positioning, and manufacturing defects playing possible causative roles. 14 Finally, Nho et al described one zirconia-on-UHMWPE femoral head fracture.…”
Section: Discussionmentioning
confidence: 99%